2019
DOI: 10.1002/ange.201907600
|View full text |Cite
|
Sign up to set email alerts
|

A Surfactant‐Free and Scalable General Strategy for Synthesizing Ultrathin Two‐Dimensional Metal–Organic Framework Nanosheets for the Oxygen Evolution Reaction

Abstract: Metal-organic framework (MOFs) two-dimensional (2D) nanosheets have many coordinatively unsaturated metal sites that act as active centres for catalysis.T od ate,l imited numbers of 2D MOFs nanosheets can be obtained through topdown or bottom-up synthesis strategies.Herein, we report a2D oxide sacrifice approach (2dOSA) to facilely synthesizeultrathin MOF-74 and BTC MOF nanosheets with af lexible combination of metal sites,whichc annot be obtained through the delamination of their bulk counterparts (top-down)o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 60 publications
1
42
0
Order By: Relevance
“…MOLs and MOFs have been widely investigated in a variety of electrocatalysis studies such as the hydrogen evolution reaction (HER), 5 , 88 , 89 , 91 95 oxygen evolution reaction (OER), 32 , 54 , 57 , 87 , 96 99 overall water splitting, 33 , 100 oxygen reduction reaction (ORR), 101 104 carbon dioxide reduction (CO 2 RR), 35 , 105 107 and electrocatalytic transformation of organic molecules. 34 , 108 Some reported MOLs show comparable or even better performance than benchmark noble metal-based catalysts.…”
Section: Facilitating Electron Transfer Of Mols For Electrocatalysismentioning
confidence: 99%
“…MOLs and MOFs have been widely investigated in a variety of electrocatalysis studies such as the hydrogen evolution reaction (HER), 5 , 88 , 89 , 91 95 oxygen evolution reaction (OER), 32 , 54 , 57 , 87 , 96 99 overall water splitting, 33 , 100 oxygen reduction reaction (ORR), 101 104 carbon dioxide reduction (CO 2 RR), 35 , 105 107 and electrocatalytic transformation of organic molecules. 34 , 108 Some reported MOLs show comparable or even better performance than benchmark noble metal-based catalysts.…”
Section: Facilitating Electron Transfer Of Mols For Electrocatalysismentioning
confidence: 99%
“…Zhang and co-workers reported a film made by Co-TCPP(Fe) MOF nanosheets, which exhibited high catalytic activity toward the reduction of H 2 O 2 , surpassing that of natural heme protein-constructed sensors . These unique properties have tremendously stimulated research on the devising of innovative synthesis routes toward 2D nanostructured MOF materials (Wang et al, 2019a;Zhuang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the introduction of CUMSs has been applied as highly active catalytic sites for catalysis, separation, and sensing. 101,114 The CUMSs can expose more active sites and act as catalytic centers, which can be beneficial to the adsorption of reactants to enhance electrocatalysis.…”
Section: Coordinatively Unsaturated Metal Sitesmentioning
confidence: 99%
“…Recently, the Zhuang group reported a facile fabrication of ultrathin MOF-74 nanosheets (NSs) with rich CUMs (FeCo-MNS-1.0) through 2D oxide sacrifice approach (2dOSA). 114 The CUMs played an active role for OER, which maximized the exposure of metal active center. The ex situ extended X-ray absorption fine structure (EXAFS) showed that the coordination numbers (C.N.)…”
Section: Coordinatively Unsaturated Metal Sitesmentioning
confidence: 99%